2018
DOI: 10.1002/eap.1651
|View full text |Cite
|
Sign up to set email alerts
|

Landscape simplification reduces classical biological control and crop yield

Abstract: Agricultural intensification resulting in the simplification of agricultural landscapes is known to negatively impact the delivery of key ecosystem services such as the biological control of crop pests. Both conservation and classical biological control may be influenced by the landscape context in which they are deployed; yet studies examining the role of landscape structure in the establishment and success of introduced natural enemies and their interactions with native communities are lacking. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 55 publications
1
54
2
2
Order By: Relevance
“…In the year with lower CLB abundance (2015), I observed a significant increase of parasitism associated with an increased proportion of major host crops at multiple scales. Contrary to our finding, Grab et al (2018) reported negative associations between the proportion of crops and tarnished plant bug parasitism by the introduced parasitoid Peristenus digoneutis Loan (Hymenoptera: Braconidae). The same authors concluded that the higher proportion of seminatural habitat in the surrounding landscape was a key factor for explaining tarnished plant bug parasitism.…”
Section: Indirect Effects Of Landscape Complexity On Cereal Leaf Beetlecontrasting
confidence: 99%
See 3 more Smart Citations
“…In the year with lower CLB abundance (2015), I observed a significant increase of parasitism associated with an increased proportion of major host crops at multiple scales. Contrary to our finding, Grab et al (2018) reported negative associations between the proportion of crops and tarnished plant bug parasitism by the introduced parasitoid Peristenus digoneutis Loan (Hymenoptera: Braconidae). The same authors concluded that the higher proportion of seminatural habitat in the surrounding landscape was a key factor for explaining tarnished plant bug parasitism.…”
Section: Indirect Effects Of Landscape Complexity On Cereal Leaf Beetlecontrasting
confidence: 99%
“…Plecas et al (2014) found a positive association between landscape complexity and aphid parasitism in two out of four years of their study, suggesting temporal variation in the response of parasitoid to the landscape complexity. Similarly, Grab et al (2018) found lower tarnished plant bug, Lygus lineolaris (Palisot de Beauvois) (Hemiptera: Miridae) parasitism by Peristenus wasps (Hymenoptera: Braconidae) in strawberry fields within simple landscapes dominated by agricultural fields (e.g., landscapes with low proportion of semi-natural area), suggesting that semi-natural habitats may provide parasitoids with important resources (nectar) that elevate their levels of parasitism. Zaller et al (2009) reported that higher crop abundance, pollen beetle abundance, and length of the roadside ditch were positively associated with rape pollen beetle parasitism at the 250 m spatial scale, suggesting that local scale complexity is important in explaining herbivore abundance in oilseed rape fields.…”
Section: Landscape and Local Scale Complexity Effects On Parasitismmentioning
confidence: 98%
See 2 more Smart Citations
“…Agricultural intensification is often characterized by monocultures that spread over extensive areas, creating highly homogeneous landscapes (He et al, 2019). Monocultures that dominate vast areas are especially prone to suffer from pest damage (He et al, 2019; Redlich, Martin, & Steffan-Dewenter, 2018), because spatial and biotic homogenization favors the spread and success of specialist pests and also removes natural habitats that host potential natural enemies (Grab, Danforth, Poveda, & Loeb, 2018; Rusch et al, 2016). In this sense, only natural enemies that tolerate the micro-environmental conditions of the culture, or that span/forage in large areas, can be effective pest control agents in landscape-dominant cultures.…”
Section: Introductionmentioning
confidence: 99%